2014
DOI: 10.1080/01635581.2014.951736
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol Causes Alterations in the Cell Cycle in Androgen Insensitive Human Prostate Cancer CellsIn Vitroby Affecting Expression of Key Cell Cycle Regulatory Proteins

Abstract: Prostate cancer, one of the most common cancers in the Western world, affects many men worldwide. This study investigated the effects of magnolol, a compound found in the roots and bark of the magnolia tree Magnolia officinalis, on the behavior of 2 androgen insensitive human prostate cancer cell lines, DU145 and PC3, in vitro. Magnolol, in a 24-h exposure at 40 and 80 μM, was found to be cytotoxic to cells. Magnolol also affected cell cycle progression of DU145 and PC3 cells, resulting in alterations to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…et al reported that MAG suppressed the metastatic property of PC-3 cells via downregulation of MMP-2, -9 both at the transcriptional and translational levels [153]. In vitro studies on androgen insensitive prostate cancer cell lines DU 145 and PC3 cells disclosed that MAG treatment causes cytotoxicity and affects the cell cycle progression by arresting the cells at the G2/M phase of the cell cycle by suppressing the expression of cell cycle regulatory proteins such as cyclin-A, -B1, -D1 and -E, and kinases like CDK-2 and CDK-4 [55]. The same research team performed another preclinical study on LNCap and PC3 cells and revealed that treatment with MAG downregulated the expression of Insulin-like growth factor-1 (IGF-1) and associated proteins such as insulin-like growth factor binding Protein-5 (IGFBP-5) and IGFBP-4 (Table 1) [151].…”
Section: Effect Of Magnolol In Different Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…et al reported that MAG suppressed the metastatic property of PC-3 cells via downregulation of MMP-2, -9 both at the transcriptional and translational levels [153]. In vitro studies on androgen insensitive prostate cancer cell lines DU 145 and PC3 cells disclosed that MAG treatment causes cytotoxicity and affects the cell cycle progression by arresting the cells at the G2/M phase of the cell cycle by suppressing the expression of cell cycle regulatory proteins such as cyclin-A, -B1, -D1 and -E, and kinases like CDK-2 and CDK-4 [55]. The same research team performed another preclinical study on LNCap and PC3 cells and revealed that treatment with MAG downregulated the expression of Insulin-like growth factor-1 (IGF-1) and associated proteins such as insulin-like growth factor binding Protein-5 (IGFBP-5) and IGFBP-4 (Table 1) [151].…”
Section: Effect Of Magnolol In Different Cancersmentioning
confidence: 99%
“…Numerous preclinical studies have established that MAG exerts its effect on different types of human cancers such as those of lung, prostate, breast, gall bladder, colon, skin and hepatocellular carcinoma [50,51,52,53,54,55,56,57]. The plausible molecular mechanisms liable for the anti-cancer potential of MAG are reduced cell proliferation or cell cytotoxicity, induction of apoptosis, accumulation of reactive oxygen species (ROS), induction of autophagy and activation/inactivation of various cellular signaling pathways [46].…”
Section: Introductionmentioning
confidence: 99%
“…17, 18 Magnolol induces apoptosis in the cells of many human cancers, including gallbladder cancer, non-small cell lung cancer, prostate cancer, human breast cancer, bladder cancer, colon cancer, and skin cancer. 9, 10, 11, 12, 14, 18, 19, 20, 21, 22, 23, 24 Therefore, magnolol has been suggested as a potential apoptosis-targeting drug. 25 Together, the results from the existing in vivo and in vitro studies have indicated that magnolol is a promising candidate for the development of new strategies for preventing and/or treating skin cancers in humans.…”
mentioning
confidence: 99%
“…In androgen insensitive human prostate cancer DU145 and PC3 cell lines, magnolol significantly inhibits the expression of cyclin A, cyclin B1, cyclin D1, cyclin E, CDK2, CDK4, and pRBp107 and enhances the expression of pRBp130, leading to cell cycle alternations. However, the proteins expression of p16INK4a, p21, and p27 are not changed apparently by magnolol after 24 hours administration [12].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Both magnolol and honokiol are isolated from the stem bark of a traditional Chinese herbal medicine Magnolia officinalis , which has been used for management of nervous disturbance, abdominal distention or disorders, gastrointestinal food stagnancy, and coughing and dyspnea [1]. Magnolol has showed a wide spectrum of beneficial activities, including anti-inflammation [2, 3], antimicroorganism [4, 5], antioxidation [6, 7], antiangiogenesis [8, 9], anticancer [1012], neuroprotection [13, 14], cardiovascular protection [15, 16], and lipolysis activities [17, 18]. However, there are still some differences between magnolol and honokiol in safety and toxicology, which have been reviewed by Sarrica et al (2018)[19].…”
Section: Introductionmentioning
confidence: 99%